STRATEGI PENINGKATAN PENERAPAN SISTEM E-COMMERCE UNTUK PENGEMBANGAN BISNIS PADA PELAKU USAHA ALAS KAKI RUMAHAN DI KECAMATAN CIOMAS KABUPATEN BOGOR - Muchlis, Mohamad; Abdul Halim, Muhamad (CV. Strata Persada Academia, 2024)
This research aims to analyze the application of the e-commerce system to footwear businesses in Ciomas District, Bogor Regency. This research uses the SERVQUAL and Importance Performance Analysis (IPA) methods to evaluate the level of importance and performance of e-commerce attributes. Primary data was collected through questionnaires filled out by 193 respondents selected using proportionate stratified random sampling techniques from a total population of 371 business people. Secondary data was obtained through direct observation of business operations and related documentation. The research results show that the level of importance of e-commerce attributes is higher than actual performance, indicating the need for improvement. Recommended strategies include improving supporting facilities and infrastructure, socializing e-commerce, and providing e-commerce management technicians. Implementation of this strategy aims to increase the efficiency and effectiveness of digital transactions, reduce potential losses, and support sustainable business development. This research emphasizes the importance of collective support from all business actors to realize an effective e-commerce strategy. Further research is recommended to ensure success and continuous improvement in the implementation of e-commerce in Ciomas District, Bogor Regency.